2021
DOI: 10.3389/fncom.2021.663408
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Neuronal Synchronisation in Coupled Areas

Abstract: One of the most fundamental questions in the field of neuroscience is the emergence of synchronous behaviour in the brain, such as phase, anti-phase, and shift-phase synchronisation. In this work, we investigate how the connectivity between brain areas can influence the phase angle and the neuronal synchronisation. To do this, we consider brain areas connected by means of excitatory and inhibitory synapses, in which the neuron dynamics is given by the adaptive exponential integrate-and-fire model. Our simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…The synchronisation occurs as complex behaviour emerging from the interaction between relatively simple systems (Rihani, 2002;Wolfram, 2018), known as stochastic resonance (Gammaitoni et al, 1998;Lucarini, 2019). Other examples include synchronised neurons, individually interacting as if they knew their peer's behaviour when they could not possibly (Lewis et al, 2004;Friston and Frith, 2015;Balconi et al, 2020;Protachevicz et al, 2021). It is worth noting that, while pendulums do not predict each other's states, they also do not know each other's states.…”
Section: Active Inference In An Enactive-dynamic Settingmentioning
confidence: 99%
“…The synchronisation occurs as complex behaviour emerging from the interaction between relatively simple systems (Rihani, 2002;Wolfram, 2018), known as stochastic resonance (Gammaitoni et al, 1998;Lucarini, 2019). Other examples include synchronised neurons, individually interacting as if they knew their peer's behaviour when they could not possibly (Lewis et al, 2004;Friston and Frith, 2015;Balconi et al, 2020;Protachevicz et al, 2021). It is worth noting that, while pendulums do not predict each other's states, they also do not know each other's states.…”
Section: Active Inference In An Enactive-dynamic Settingmentioning
confidence: 99%
“…But, later it was proved wrong [3] and a stable anti-phase oscillations in electrically coupled relaxation oscillators were reported [15]. The stochastic transitions between in-phase and anti-phase synchronisations in neural oscillators are still of great interest even after these many years [16,17]. Researchers have proposed different modifications in inhibitory and excitatory connections to induce anti-and in-phase oscillations [8,18].…”
Section: Introductionmentioning
confidence: 99%
“…In such a model it was reported that the generation of the action potential in the cell membrane is linked to variations in the ionic currents of potassium, sodium and a current defined by them as leak. Although varous mathematical models have been proposed to reproduce the neuronal behaviour [14,15], the HH neuron is still one of the most actual approaches to neuronal dynamics, inspiring several studies in the field of neuroscience [16,17].…”
Section: Introductionmentioning
confidence: 99%